Optical model and distorted wave analusis of (d,d) (d,p) and (d,d´) reactions on O16, Ni 58, Pb207 and Pb208 at 27.5 Mev - Testoni, J. E.; Mayo, Santos; Hodgson, P.E. (North Holland Publishing, 1964)
Fil: Testoni, J. E. Comisión Nacional de Energía Atómica; Argentina